An Isoflavone Glycoside from the Stem of Euphorbia Hirta Linn as Antimalarial Compound - Koli, M.C.; Choudhary, Rashmi; Kumar, Sourabh; Thakur, Suman; Shukla , Deepti; Shukla, R.C. (Asian Journal of Chemistry, 2010)
Euphorbia hirta Linn. of family Euphorbiaceae is found abundant in the plane areas, near rivers and on marshy lands. The whole herbs were collected from a village of Tehsil Multai district Betul a tribal area of Madhya Pradesh region during winter months. The powdered material was extracted in soxhlet uprights which gave maximum 7.66% yield in water and 3.21% in 90% alcohol. The water extract was further purified using column chromatography and TLC. An isoflavone glycoside isolated from the plant showed antimalarial activities at different concentrations.